The necropolis of Al Qusais (Dubai, UAE): preliminary results on the 2020 excavation and data reassessment from the 70s and 90s excavations - Valente, Tatiana; Contreras, Fernando; Vila, Bernardo; Fernández, Adrián; Al Ali, Bader; Radwan Karim, Mansour Boraik; Zein, Hassan Mohammed (Proceedings of the Seminar for Arabian Studies, 2023)
The site of Al Qusais has for long been forgotten until recent interest from Dubai Municipality to reassess the data uncovered in its 70s and 90s excavations. The first excavations uncovered two main areas of occupation, a Bronze and Iron Age necropolis and the so-called ‘Mound of Serpents’, where numerous copper snakes and snakes decorated ceramics were found, associated with what seems to be a columned hall building, characteristic of Iron Age II period. In the 90s, new excavations were held in the necropolis area, where 101 burial pits were found. In them, a rich assemblage of burial goods and human remains were uncovered, though never studied nor published. After almost thirty years, new excavations were thus held and data reassessed. Although the excavation could not last long, more burial pits were identified, the previously uncovered material was studied and chronologically interpreted, human remains identified, and a geomorphological and environmental study was held to understand its prehistoric landscape. The results from this 2020 reassessment and excavation that we present will hopefully help understand the “cultural” shifts that occurred from the Bronze to the Iron Age period, still so poorly understood and differentiated from one period to the other.